A Potassium Diboryllithate: Synthesis, Bonding Properties, and the Deprotonation of Benzene. (17th August 2016) - Ohsato, Takuto; Okuno, Yuri; Ishida, Shintaro; Iwamoto, Takeaki; Lee, Ka‐Ho; Lin, Zhenyang; Yamashita, Makoto; Nozaki, Kyoko
Abstract: A potassium diboryllithate (B2 LiK) was synthesized and structurally characterized. DFT calculations, including NPA and AIM analyses of B2 LiK, revealed ionic interactions between the two bridging boryl anions and Li + and K + . Upon standing in benzene, B2 LiK deprotonated the solvent to form a hydroborane and a phenylborane. On the basis of DFT calculations, a detailed reaction mechanism, involving deprotonation and hydride/phenyl exchange processes, is proposed. An NBO analysis of the transition state for the deprotonation of benzene suggests that the deprotonation should be induced by the coordination of benzene to the K + .